The Human Touch : Personal skills for professional success. - Thomas, Philippa (BCS Learning & Development Ltd., 2012)
Strong interpersonal skills are a fundamental requirement in all work environments. This book provides expert guidance for IT and other professionals on key skills including: building rapport; team working; leadership; negotiation; written communication; managing conflict; presentation skills; coaching and mentoring; problem solving.